The Influence Of The Reading Corner On Increasing Interest In PAI Material Literacy In Visual Communication Design Students At SMK Mambaul Ulum Pandaan - Rachmawati, Adinda Citra; Ma’ruf, Ahmad (-, 2025)
In today's technological developments, reading and writing literacy skills are important things that students must have. In the literacy process, it is not only about reading and writing skills, but also involves the ability to understand and analyze science. In connection with the low number of students' interest in reading, especially understanding religious material which has an impact on the less than optimal results of Islamic Religious Education learning, the existence of a reading corner can be a solution in increasing interest in reading religious material. The purpose of this study was to determine the effect of reading corners on increasing students' interest in literacy in Islamic Religious Education (PAI) subjects. This study was conducted using a quantitative approach with an experimental research type using the One Sample T-Test sample test, namely to determine whether the average of a sample is significantly different from a certain known value. The data collection process was carried out by distributing questionnaires to 13 respondents. By distributing questionnaires and processing data, it was found that reading corners had an effect on increasing interest in literacy in Islamic Religious Education materials in Visual Communication Design students at SMK Mambaul Ulum Pandaan. With this research, it is hoped that it can be a solution in increasing interest in literacy in Islamic Religious Education materials.